Upaya Peningkatan Pengetahuan untuk Pencegahan Kekambuhan pada Pasien Asma di Puskesmas 23 Ilir Palembang - Utama, Yofa Anggriani (Universitas Baiturrahim, 2025)
Asthma is a disease characterized by chronic inflammation of the respiratory tract with manifestations of respiratory complaints (wheezing, shortness of breath, and coughing) with varying expiratory airflow obstruction with varying symptom intensity, inflammation of the respiratory tract plays a role in causing airway hyperactivity, airflow obstruction, and respiratory complaints. The purpose of implementing this community service activity is to increase community knowledge regarding prevention of relapse in asthma patients. The method of implementing this community service activity was carried out in the work area of ​​the 23 Ilir Palembang Health Center on April 24, 2025. The activity was attended by 20 asthma sufferers. The results obtained were knowledge before being given education as many as 4 participants (20%) participants had good knowledge regarding prevention of asthma relapse. After being given education, there was an increase in knowledge as many as 17 participants (85%) participants had good knowledge regarding prevention of asthma relapse